A colo-colic intussusception caused by a submucosal lipoma in a child with morm infestation of the intestinal tract – a case report - Abd. Aziz, Azian; G., Samuel; A.R., M. Norhisham Azmi; A.L., Alia Maisyah (2015)
The aim of this case report is to remind clinicians and general radiologists that intussusception in older children are commonly caused by a lead point. One of the most common lead point in this instance is bowel lipoma. Intussusception without lead point most commonly occurs in infant between 4 to 10 months of age. Typically, the clinical presentation is often non-specific abdominal pain with blood mix with the stool classically described as redcurrant jelly. We are illustrating a case of an 11-year-old girl who presented to the Emergency Department with a 3-day history of colicky abdominal pain and per rectal bleed. Abdominal ultrasound examination detected an intussusception on the left side of the abdomen associated with an adjacent well defined hyperechoic mass within the bowel lumen. In addition, worms were also present within the bowel. A successful contrast reduction of the intussusception was performed but a persistent well defined filling defect within the distal transverse colon was observed. Colonoscopy revealed a mass proximal to the splenic flexure almost completely obstructing the colonic lumen. A worm bolus was also seen near the ileo-caecal junction. A limited distal transverse colectomy was performed and histology examination confirmed the colonic mass to be a submucosal lipoma.